2012
DOI: 10.1088/1009-0630/14/9/11
|View full text |Cite
|
Sign up to set email alerts
|

In vitroCyto and Blood Compatibility of Titanium Containing Diamond-Like Carbon Prepared by Hybrid Sputtering Method

Abstract: In recent years, diamond-like carbon films (DLC) have been given more attention in research in the biomedical industry due to their potential application as surface coating on biomedical materials such as metals and polymer substrates. There are many ways to prepare metal containing DLC films deposited on polymeric film substrates, such as coatings from carbonaceous precursors and some means that incorporate other elements. In this study, we investigated both the surface and biocompatible properties of titaniu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 26 publications
0
14
1
Order By: Relevance
“…The C1s spectra were deconvoluted by Gauss‐Lorentz curves, corresponding to the peaks of C–Ti (only in case of the carbon‐titanium composite layers), C‐Si, sp 2 phase, sp phase, C‐O, and C=O bounds. Obtained peak maxima were around 281.9 eV, 284.2 eV, 284.5 eV, 285.3 eV, 286.1 eV, 288 eV, respectively …”
Section: Methodsmentioning
confidence: 96%
“…The C1s spectra were deconvoluted by Gauss‐Lorentz curves, corresponding to the peaks of C–Ti (only in case of the carbon‐titanium composite layers), C‐Si, sp 2 phase, sp phase, C‐O, and C=O bounds. Obtained peak maxima were around 281.9 eV, 284.2 eV, 284.5 eV, 285.3 eV, 286.1 eV, 288 eV, respectively …”
Section: Methodsmentioning
confidence: 96%
“…The increased thromboresistivity of DLC films deposited by the radio frequency plasma enhanced CVD method and treated with plasma of oxygen gas has been discussed in [86]. The experiments show the strong dependency of DLC properties on the deposition conditions and doping effects [80,[87][88][89]. The results concerning in vivo testing and medical studies of DLC coated stents can be found in several papers [80,[90][91][92].…”
Section: Diamond-like Carbon (Dlc) Coatingsmentioning
confidence: 99%
“…For example, they have been widely used in packaging, furniture, toys, automobiles, food and beverage containers, biomedical implants, and solar power devices. Among polymers, Polyethylene terephthalate (PET) holds diverse applications as cardiovascular implants (artificial heart valves and blood vessels), food and beverage containers, and components in solar cells [1][2][3]. PET is a semicrystalline polymer with a simple long chain belong to polyester family and possesses outstanding properties like chemical inertness, high mechanical strength, toughness, and fatigue resistance.…”
Section: Motivationsmentioning
confidence: 99%
“…These materials range from diamonds that have super high hardness and extremely high thermal conductivity, to graphite, which is very soft and can be used as a solid lubricant. Carbon has the ability to be in three different electronic configurations, sp 1 , sp 2 and sp 3 , which is the source of its unique behaviors [16]. Carbon has six electrons, which are configured as 1s 2 2s 2 2p 2 and illustrated in The electron distribution of carbon makes it possible to form different allotropes with three bonding configurations, as well as the ability to form single, double and triple bonds.…”
Section: Carbon Materialsmentioning
confidence: 99%
See 1 more Smart Citation